Naproxen chemoprevention promotes immune activation in Lynch syndrome colorectal mucosa. Issue 3 (8th July 2020) - Reyes-Uribe, Laura; Wu, Wenhui; Gelincik, Ozkan; Bommi, Prashant V; Francisco-Cruz, Alejandro; Solis, Luisa M; Lynch, Patrick M; Lim, Ramona; Stoffel, Elena M; Kanth, Priyanka; Samadder, N Jewel; Mork, Maureen E; et al.
Abstract : Objective: Patients with Lynch syndrome (LS) are at markedly increased risk for colorectal cancer. It is being increasingly recognised that the immune system plays an essential role in LS tumour development, thus making an ideal target for cancer prevention. Our objective was to evaluate the safety, assess the activity and discover novel molecular pathways involved in the activity of naproxen as primary and secondary chemoprevention in patients with LS. Design: We conducted a Phase Ib, placebo-controlled, randomised clinical trial of two dose levels of naproxen sodium (440 and 220 mg) administered daily for 6 months to 80 participants with LS, and a co-clinical trial using a genetically engineered mouse model of LS and patient-derived organoids (PDOs). Results: Overall, the total number of adverse events was not different across treatment arms with excellent tolerance of the intervention. The level of prostaglandin E2 in the colorectal mucosa was significantly decreased after treatment with naproxen when compared with placebo. Naproxen activated different resident immune cell types without any increase in lymphoid cellularity, and changed the expression patterns of the intestinal crypt towards epithelial differentiation and stem cell regulation. Naproxen demonstrated robust chemopreventive activity in a mouse co-clinical trial and gene expression profiles induced by naproxen in humans showed perfect discrimination of mice specimens with LS and PDOs treated with naproxen and control. Conclusions: Naproxen is a promising strategy for immune interception in LS. We have discovered naproxen-induced gene expression profiles for their potential use as predictive biomarkers of drug activity. Trial registration number: gov Identifier: NCT02052908